(untitled) (Conferencea, 2022)
In the research, the translator is considered as a living, active and biased subject of discursive activity. The mechanisms underlying his activity in interpreting the text and the world of the work are modeled in terms of systemic relationships and synergistic interactions within the construction of translation (inter)discourse. The author uses general scientific methods of analysis, synthesis, description, modeling, reconstruction, comparison, systemic and structural-functional methods.